Urban Soils in Gainesville, Florida, and Their Implications for Environmental Quality and Management - Donald Hagan; Cynnamon Dobbs; Francisco Escobedo; Wayne Zipperer; Zoltan Szantoi (EDIS)
It is frequently assumed that urban soils are homogenous, heavily disturbed, or of low fertility. But recent studies show that urban soils are highly variable, ranging from highly modified to nearly undisturbed. Still, there are observable trends and patterns in urban soil characteristics have been observed. This 6-page fact sheet sheds light on how and why soil properties vary across Gainesville and provides useful information on the sustainable management of urban soils. It was written by Donald Hagan, Cynnamon Dobbs, Francisco Escobedo, Wayne Zipperer, and Zoltan Szantoi, and published by the UF Department of School of Forest Resources and Conservation, November 2010.